O jornalismo literário - Ferreira, Héris Arnt Telles (1990)
In the 19th century, one particular characteristic dominated journalism in several parts in the world: the active participation of writers in newspapers, either as publishers, chroniclers and aditorialists or as feuillatoniste. The result of their influence is what may be called Literary Journalism. Precise information about habits and customs as well as political and parlamentary life can be found in chronicles of that time. Feuilletons made social and economical criticism subtly and deeply. However, not only writers shaped journalism. Literature also benefited from the close connection with journalism, determining a narrative form that favored action rather than reflexion.